Risk and cost of infection-related hospitalizations in medicare beneficiaries with comorbid rheumatoid arthritis treated with abatacept versus other targeted disease-modifying anti-rheumatic drugs. (1st January 2021) - Patel, Vardhaman; Pulungan, Zulkarnain; Shah, Anne; Kambhampati, Mahesh; Lobo, Francis; Petrilla, Allison
Abstract: Objective: This study evaluated infection-related hospitalization risk and cost in tumor necrosis factor inhibitor (TNFi)-experienced and targeted DMARD (tDMARD) naïve rheumatoid arthritis (RA) patients that were treated with abatacept, TNFi, or other non-TNFi. Methods: This retrospective study used 100% Medicare Fee-for-Service claims to identify patients ≥65 age, diagnosed with RA, and were either 1) TNFi-experienced, who switched from a TNFi to another tDMARD (subsequent tDMARD claim served as index), or 2) tDMARD naïve (first therapy claim served as index), who initiated either abatacept, TNFi, or non-TNFi as their first tDMARD, between 2010 and 2017. Follow-up ended at the date of disenrollment, death, end of study period, or end of index treatment, whichever occurred first. Infection-related hospitalizations included pneumonia, bacterial respiratory, sepsis, skin and soft tissue, joint or genitourinary infections. A Cox proportional hazard model and two part generalized linear model were developed to estimate adjusted infection-related hospitalization risk and costs. Costs were normalized to per-patient-per-month (PPPM) and inflated to 2019 US. Results: The infection-related hospitalizations rate was lower during follow-up than during baseline periods for abatacept users, but was reversed for both TNFi and other non-TNFi users in both TNFi-experience and tDMARD naïve ( p value < .001 based on Breslow-Day test for homogeneity of odds ratios). Infection-related hospitalization PPPM cost was significantly lower in abatacept treated patients compared to TNFi (TNFi-experienced: by 74; tDMARD naïve: 42) and other non-TNFi (TNFi-experienced: by 68; tDMARD naïve: 60). The adjusted infection-related hospitalization risk was significantly higher for RA patients treated with TNFi (TNFi-experienced HR: 1.48; 95% CI: 1.26–1.75, p < .0001; tDMARD naïve HR:1.59; 95% CI: 1.43–1.77, p < .0001) and other non-TNFi (TNFi-experienced HR:1.46; CI:1.28–1.66; tDMARD naïve HR:1.63; 95% CI: 1.44–1.83) than with abatacept. Conclusion: RA Medicare Fee-For-Service beneficiaries who either switched or initiated abatacept have a lower infection-related hospitalization risk and cost compared to patients who switched to or initiated other tDMARDs.